Pengaruh Usia Ibu Hamil Terhadap Kejadian Placenta Previa Di RSUP Soeradji Tirtonegoro - Yeni Tutu Rohimah (Poltekkes Kemenkes Surakarta, 2016)
Abstract : Maternal Age, Placenta Previa. Maternal Mortality Rate (MMR), is one of State Health Development Indicators. Indonesia MMR in the first level in Asean. Bleeding is the cause of MMR,placenta Previa is cause of bleeding, the incidence of placenta previa is 0.3-0.5% of all births, the risk of placenta previa associated with age of the women during pregnancy. Incidence increased as follows : 12-19 years - 1%, 20-29 years - 0.33%, 30-39 years - 1%, above 40 years - 2%. Incidenceof placenta previa in Soeradji Tirtonegoro HospitalKlaten in 2010 there were 122 cases. Thestudyused the Ex Post Facto, the population in this study is the maternal with plecentaprevia, the sample used a total sample of 122 maternal with placenta previa in 2010. Devendent variable in this study is placenta previa,independt variable is the maternal age, the studyin Dr Soeradji Tirtonegoro Hospital Klaten. Analysis used the linear regression.The effect of maternal age on the incidence of plcentsprevisis significantp = 0.000 (p<0.05), 87.20% incidence of placenta previa is influenced by maternal age and the effect is very strong r = 0.938. Each additional 1 year of maternal age increases the incidence of placenta previa 1,332 cases